Cassava agronomy research and adoption of improved practices in Thailand: Major achievements during the past 35 years - Tongglum, Anuchit; Suriyapan, Preecha; Howeler, Reinhardt H. (International Center for Tropical Agriculture, 2001)
This paper reviews the results of past research conducted from 1965 to 2000 in two major cassava growing areas, the northeastern and eastern parts of Thailand. This research was carried out by the Field Crops Research Institute, Department of Agriculture (DOA), in collaboration with Kasetsart University and the Centro Internacional de Agricultura Tropical CIAT). The major achievements are described under the following three topics: Methods of cultivation, which tested and developed all the necessary components of cassava cultural practices, such as land preparation, planting time, age of harvest, spacing and plant population, planting method, stake size and storage, as well as weed control. Cassava-based cropping systems, which showed the feasibility of intercropping cassava with short-duration crops such as mungbean, peanut, soybean and sweet corn. Cassava soil conservation and fertility maintenance, which tested and developed appropriate production practices that both reduce soil loss by erosion and maintain high cassava yields. Long-term experiments on the effect of various fertilizer applications and soil management treatments showed the crop’s nutritional requirements, and indicate soil/crop management practices that will maintain high levels of cassava productivity as well as adequate soil fertility.